One dimensional CdS based materials for artificial photoredox reactions. Issue 6 (13th January 2017) - Tang, Zi-Rong; Han, Bin; Han, Chuang; Xu, Yi-Jun
Abstract : The design and construction of 1D CdS based photocatalysts with boosted performance have been elaborately reviewed, and some challenges and opportunities for the future exploration in this arena are discussed. Abstract : Semiconductor-based heterogeneous photocatalysis has received considerable attention as an alternative promising approach to alleviate the globally increasing energy demand and environmental concerns. As promising candidates, one dimensional (1D) CdS nanostructures have gained growing interest due to their unique advantages, including a narrow band gap, suitable band edge positions, high aspect ratio structure with low reflectance, and excellent electronic charge transfer. This review summarizes a panorama of the latest progress related to the design and construction of 1D CdS based photocatalysts with boosted performance, involving constructing 1D solid solution, loading cocatalysts, coupling with semiconductors, hybridizing with carbon-based materials and functionalization with biocatalysts. Finally, some challenges and opportunities for future exploration of 1D CdS based photocatalysts are critically discussed. It is anticipated that this review will afford enriched information on the rational utilization of 1D CdS materials with ameliorated performances by harnessing their inherent merits, and particularly stimulate further developments of low dimensional heterostructures towards various artificial photoredox reactions.